Incidence of pressure ulcer and risk assessment using the ELPO scale: observational study (Research, Society and Development, 2021)
Objective: To evaluate the risk for developing pressure ulcers and its incidence in the surgical center of a University Hospital in Rio de Janeiro by using the risk assessment scale for the development of injuries resulting from surgical positioning of the patient (ELPO). Methodology: Cohort observational descriptive exploratory study with quantitative analysis. Data collected between september and november 2018 in three steps: preoperative nursing visit, evaluation of the perioperative moment and postoperative follow-up. Results: Fifty two patients included in the study, 18 (34,6%) were classified as high risk by the ELPO and 34 (65,4%) as low risk. Of the patients evaluated, four (8%) evolved with one pressure ulcer each in the immediate postoperative period after surgeries that lasted more than 4 hours, under general anesthesia and mostly in the supine position. The incidence of these injuries was 7.69%. Conclusion: The scale was useful for risk assessment and allowed to optimize preventive actions for pressure ulcer. It is recommended the need to use the ELPO scale in clinical practice in order to predict the risk of developing pressure ulcer in surgical patients and the implementation of preventive measures related to each surgical situation.